Elevating phosphorus accumulation in waste stabilisation pond algae : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Environmental Engineering at Massey University, Palmerston North, New Zealand - Sells, Matthew (Massey University, 2019)
Facultative waste stabilisation ponds (WSP) are used globally for wastewater treatment due to their low cost and simple operation. While WSPs can be effective at removing organic pollutants and pathogens, phosphorus removal is typically poor. Algae that are common in WSPs are known to accumulate phosphorus and increase their phosphorus content in the biomass from 1% up to 3.8% (gP/gSS), which is believed to be from the production of intracellular polyphosphate granules. This phenomenon, known as luxury uptake, may be possible to manipulate to improve phosphorus removal in WSPs; however, its occurrence is sporadic and poorly understood. This PhD thesis was undertaken to investigate the conditions that influence phosphorus accumulation in WSP algae. Phosphorus accumulation was quantified using two methods: (1) the traditional phosphorus content in the biomass (gP/gSS), and (2) a new image analysis method developed in this thesis that quantifies stained polyphosphate granules within individual algal cells (μm2 granule/μm2 cell). Following a literature review and screening experiments that sought to identify variables that could affect the phosphorus content in the biomass (gP/gSS), six variables: temperature, phosphorus concentration, light intensity, mixing intensity, organic load, and pH were comprehensively examined using 40 batch factorial experiments (26-1) and a mixed genus culture from a full-scale WSP. Nine variables and interactions had a significant effect on the phosphorus content in the biomass and were incorporated into a regression equation. This ‘mixed genus’ regression equation was tested against literature data, where seven out of the eight batch experiments from the literature were successfully predicted. In order to identify if the batch findings could be applied to a continuous process, which is more typical of full-scale WSPs, a bench-scale novel ‘luxury uptake’ process was designed, built, and operated under five different scenarios. The regression equation successfully predicted the experimental results for three of the five conditions examined. It was theorised that differences in behaviour at the genus level might explain why all five conditions were not successfully predicted. In an attempt to improve the prediction capability, the ‘black-box’ of mixed genus analysis was ‘opened’ to allow the effects of variables on phosphorus accumulation at the genus level to be directly examined. To achieve this, a new image analysis method was developed that quantified stained polyphosphate granules in individual algal cells. To ensure the granules being measured were indeed polyphosphate, algal cells were analysed using transmission electron microscopy coupled with energy dispersive X-ray spectroscopy, which confirmed the granules contained higher levels of phosphorus compared to the remaining cell. The image analysis method was then used to quantify stained polyphosphate granules in individual cells from the 40 batch factorial experiments mentioned previously. The results using the image analysis method showed that, for the five most abundant algal genera, Micractinium/Microcystis had the highest average accumulation of polyphosphate granules (17% μm2 granule/μm2 cell), followed by Scenedesmus (12%), Pediastrum (11%), Monoraphidium (8%), and Actinastrum (4%). Although none of the genera studied had the same combination of significant variables, all five genera preferred a high phosphorus concentration to elevate polyphosphate granule accumulation. Furthermore, a high light intensity, high organic load, or high temperature was preferred by the algae if the variable was significant for that genus. The culture used in the bench-scale continuous flow ‘luxury uptake’ process originated from a mixed genus WSP culture; however, it had become dominated by the Scenedesmus genus. Therefore, the regression equation was refined to use the batch data for this genus alone. This new Scenedesmus regression equation was compared against the experimental data from the ‘luxury uptake’ process previously mentioned. Polyphosphate granule accumulation was now successfully predicted in all five experimental conditions at the 95% confidence level. This improved prediction capability indicates that an understanding of the algal genus present in a WSP system is required for accurate predictions of the phosphorus accumulation to be obtained, and the batch data can indeed be applied to a continuous process. An unexpected result of the research was that, contrary to what was believed in the literature, an increase in the phosphorus content in the biomass did not necessarily increase the polyphosphate granule accumulation. Further examination identified that individual cells from the same algal species had varying polyphosphate granule contents from 0% to over 20% (μm2 granule/μm2 cell) when exposed to the same conditions. This variation was hypothesised to be from cellular functions influencing the granules differently depending on the individual alga’s cell cycle. In addition, when the phosphorus content in the biomass was increased above 2.1% (gP/gSS), no significant effect on the average quantity of polyphosphate granules was observed. This finding indicates that other forms of phosphorus storage must be responsible for attaining a highly elevated phosphorus content in the biomass.
Keywords: Sewage lagoons; Sewage; Purification; Phosphate removal; Polyphosphates; Bioaccumulation; Algae; Metabolism